Adding another piece to the cynipoid puzzle: the description of a new tribe, genus and species of gall wasp (Hymenoptera: Cynipidae) endemic to The Republic of South Africa - Liljeblad, Johan; Nieves-Aldrey, José Luis; Neser, Stefan; Melika, George (Zootaxa, 2011)
Larvae and adult females of a single species inducing galls on Scolopia mundii (Salicaceae) are described as Qwaqwaia scolopiae Liljeblad, Nieves-Aldrey & Melika sp. n. The genus Qwaqwaia Liljeblad, Nieves-Aldrey & Melika gen. n. is also described as new and placed in a tribe, Qwaqwaiini Liljeblad, Nieves-Aldrey & Melika trib. n., herein erected to encompass this sole species. Diagnostic characters and a key to all eight cynipid tribes are given. With its unique South African distribution and seemingly plesiomorphic morphology, this gall wasp is important for the future untangling of the early evolution of the microcynipoids.